A history of the Japanese people - Brinkley, F. (Frank), 1841-1912; Kikuchi, Dairoku, 1855-1917 (Salt Lake City, UT : Project Gutenberg, 2008)
"A History of the Japanese People: From the Earliest Times to the End of the Meiji Era" by Capt. F. Brinkley is a historical account written in the early 20th century. The text examines Japanese history through various cultural, political, and social lenses, tracing the development of the nation from its early origins to the close of the Meiji era. The book is notable for its integration of mythology, legends, and historical facts, providing a comprehensive overview of Japan's remarkable transformation during this period. The opening of the book sets the stage for exploring the historiography of Japan, emphasizing the significance of understanding a nation's history to appreciate its culture fully. It outlines the initial roles of storytellers in ancient Japan, who recounted the deeds of emperors and heroes before writing was introduced. Capt. Brinkley discusses the compilation of early historical texts such as the "Nihon Shoki" and the "Kojiki," explaining how the transition from oral to written history occurred. The foreword and author's preface collectively highlight the importance of historical accuracy and cultural context in modern interpretations of Japan's past. (This is an automatically generated summary.)
Release date is 2008-12-23
E-text prepared by Geoffrey Berg from digital material generously made available by Internet Archive (http://www.archive.org)
Keywords: Japan -- Civilization; Japan -- History